STUDENTSâ PREFERENCES TOWARD CORRECTIVE FEEDBACKS ON STUDENTSâ ORAL PRODUCTION - fitriana, rinda (Script Journal: Journal of Linguistic and English Teaching, 2016)
This study aimed on revealing studentsâ preference on types of corrective feedback given by their English teacher as well as their reason. The study was conducted in a vocational school in Samarinda. Data collection was done by means of observation, interview and questionnaire. The observation was done for three meetings each in two different level of English proficiency classes (high and low) and ten students from the observed classes were interviewed. Moreover, the questionnaires were administered to 196 out of 385 students from all classes of twelfth grade. Furthermore, the result of this study revealed that the students preferred to have Explicit, Meta-Linguistic Clue and Elicitation corrective feedback. However, there was mismatch between studentsâ preference on the expected type corrective feedback (Explicit) and the teacherâs corrective feedback (Recast). The studentsâ preference on explicit corrective feedback was based on the reason that it provided answer and explanation on the correct version of the corrected oral production. The studentsâ preference on Meta-linguistic Clue and Elicitation corrective feedback were because these feedbacks activated their knowledge and generated studentsâ thinking to discover the correct version.